STRATEGIC POSITIONING OF AGRICULTURAL FINANCIAL PRODUCTS - Tzvetelina Borisova (Journal of Bio-Based Marketing)
The positioning ideology in the presented theory is based on the study of various determinants creating loyal demand for the company’s product. Of course, the theory has evolved by now, but the idea remains unchanged, namely creating user addictions. This requires the followers of the theory, as well as all researchers of the problem, to connect positioning with the science of personality psychology. Today, thanks to internet connectivity, smart mobile devices, and the Internet of Things, positioning is done by creating complex patterns of consumer behavior for goods and services. If in the 80s of the last century, the market was perceived as a set of separate groups of consumers (market segments) with similar needs, then today the individual is perceived as a separate market, as a set of needs that are graded and prioritized differently.